The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1001/jama.2015.1405
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Concordance Among Pathologists Interpreting Breast Biopsy Specimens

Abstract: IMPORTANCE A breast pathology diagnosis provides the basis for clinical treatment and management decisions; however, its accuracy is inadequately understood. OBJECTIVES To quantify the magnitude of diagnostic disagreement among pathologists compared with a consensus panel reference diagnosis and to evaluate associated patient and pathologist characteristics. DESIGN, SETTING, AND PARTICIPANTS Study of pathologists who interpret breast biopsies in clinical practices in 8 US states. EXPOSURES Participants i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
427
2
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 550 publications
(456 citation statements)
references
References 33 publications
(34 reference statements)
7
427
2
1
Order By: Relevance
“…Previous studies have shown that breast atypia is consistently the most challenging diagnostic category for pathologists. 3,[12][13][14] Thus, even if a pathologist reviews a critical image region, recognizing architectural and cytologic features of atypia and accurately assimilating these features into a diagnostic rubric can be challenging.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that breast atypia is consistently the most challenging diagnostic category for pathologists. 3,[12][13][14] Thus, even if a pathologist reviews a critical image region, recognizing architectural and cytologic features of atypia and accurately assimilating these features into a diagnostic rubric can be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…The methods for test case identification and the development and recruitment of pathologists have been previously described. 3,7 Briefly, single, representative diagnostic slides from excisional or core breast biopsies of 180 women were included in this pilot study. Each slide was digitally scanned (iScan Coreo, Ventana Medical Systems, Tucson, AZ, USA), and a whole slide image (WSI) was created, allowing the digital virtual slide to be viewed, magnified, and annotated on a computer using a web-based viewer.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Manual counting of mitosis is a tedious process and often prone to inter-and intra-reader variations. A recent concordance study for quantifying the magnitude of diagnostic disagreement among pathologists on breast biopsy specimens reported 27.7% overall disagreement between the individual pathologists' interpretations and the expert consensus-derived reference diagnoses [5]. A mitosis has four main phases of prophase, metaphase, anaphase and telophase, and exhibits highly variable appearance.…”
Section: Introductionmentioning
confidence: 99%